2008
DOI: 10.1038/ncb1812
|View full text |Cite
|
Sign up to set email alerts
|

MG53 nucleates assembly of cell membrane repair machinery

Abstract: Dynamic membrane repair and remodelling is an elemental process that maintains cell integrity and mediates efficient cellular function. Here we report that MG53, a muscle-specific tripartite motif family protein (TRIM72), is a component of the sarcolemmal membrane-repair machinery. MG53 interacts with phosphatidylserine to associate with intracellular vesicles that traffic to and fuse with sarcolemmal membranes. Mice null for MG53 show progressive myopathy and reduced exercise capability, associated with defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
703
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 408 publications
(733 citation statements)
references
References 37 publications
27
703
2
1
Order By: Relevance
“…Our previous studies showed that MG53 can function in the repair of sarcolemmal membrane following acute cell injury (22). Those finding are consistent with our observation here that MG53 participates in vesicle trafficking in the course of normal cellular physiology.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our previous studies showed that MG53 can function in the repair of sarcolemmal membrane following acute cell injury (22). Those finding are consistent with our observation here that MG53 participates in vesicle trafficking in the course of normal cellular physiology.…”
Section: Discussionsupporting
confidence: 93%
“…1C, left panels). This result is consistent with our electron microscopic localization of MG53 in skeletal muscle fibers (22) and suggests that MG53 may participate in membrane trafficking events in muscle cells.…”
Section: Overexpression Of Mg53 Producessupporting
confidence: 92%
See 3 more Smart Citations